2008
DOI: 10.1002/pros.20755
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine profiling of prostatic fluid from cancerous prostate glands identifies cytokines associated with extent of tumor and inflammation

Abstract: BACKGROUND-Cytokines are key mediators of inflammation that may play important roles in prostate cancer initiation and progression. Cytokines found in cancerous prostates may provide further insight into the mechanisms of cancer initiation and progression, and facilitate the exploration of new markers of prostatic neoplasia and inflammation. We describe the cytokine profile of prostatic fluids obtained from cancerous prostate glands and correlate it to both cancer status and inflammation grade.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 32 publications
2
35
0
2
Order By: Relevance
“…these results are consistent with previous studies that found that plasma levels of tnF-α, Il-10 and Il-18 are increased in advanced-stage Hcc (36-41). similar results have also been reported for advanced-stage gastric cancer (42-45) and prostate cancer (46). these previous results combined with our present results strongly indicate that higher levels of plasma tnF-α, Il-10 and Il-18 correlate to a poor prognosis in cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…these results are consistent with previous studies that found that plasma levels of tnF-α, Il-10 and Il-18 are increased in advanced-stage Hcc (36-41). similar results have also been reported for advanced-stage gastric cancer (42-45) and prostate cancer (46). these previous results combined with our present results strongly indicate that higher levels of plasma tnF-α, Il-10 and Il-18 correlate to a poor prognosis in cancer patients.…”
Section: Discussionsupporting
confidence: 92%
“…The massive secretion of IL-6 in the pancreas of ENO1-vaccinated mice (data not shown) may explain the increase of Th17 rather than FoxP3 ϩ cells. 24 Th17 cells recruit neutrophils and eosinophils, 25 also present in pancreatic tumor lesions from empty-vaccinated mice (data not shown), and this native immune response partly impeded tumor progression, particularly at the beginning; indeed, at 24 weeks of age, both empty-and ENO1-vaccinated mice presented a lower percentage of transformed pancreatic ducts compared with untreated mice. However, only the combination of the innate and acquired immune responses induced by ENO1 vaccination was able to significantly delay tumor progression.…”
Section: Pancreasmentioning
confidence: 92%
“…ICAM-1 has an important role in enhancing T cell killing via cell-cell adhesion to lymphocyte function-associated antigen (LFA)-1 and by directly co-stimulating activated T cells (Garnett et al, 2004;Baluna et al, 2006). PCa cells express ICAM-1 and VCAM-1 and in tissue areas of high lymphocyte and neutrophil accumulation the expression of ICAM-1 is significantly elevated (Fujita et al, 2008;Rokhlin & Cohen, 1995). These data suggest that ICAM-1 upregulation by IR may facilitate immune responses by recruiting lymphocytes and macrophages to the tumour site.…”
Section: Irradiated Tumour Cells Become Sensitive To Immune Cell Attackmentioning
confidence: 99%
“…IL-12 is secreted by mature DC and macrophages and required for IFN and TNF production from T cells and mediates a Th1-type immune response. Adenovirus-derived IL-12 plus RT significantly increased local antitumour and systemic antimetastatic effects in a preclinical model of metastatic PCa when compared to either treatment alone (Fujita et al, 2008). This antimetastatic activity is due to the antitumoural activities of natural killer (NK) cells.…”
Section: Pre-clinical Modelsmentioning
confidence: 99%